2021
DOI: 10.26681/jote.2021.050106
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Anatomy Coursework and Perceptions of Occupational Therapy Students: A Survey Study

Abstract: Occupational therapy practitioners utilize their knowledge of human anatomy to understand underlying anatomical dysfunction and how it impacts occupational performance. However, anatomy is not a required standalone course within occupational therapy curricula. This may leave students at a disadvantage throughout occupational therapy programs, fieldwork, and as practitioners. The primary purpose of this study was to explore graduate level occupational therapy students' previous anatomy undergraduate coursework,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…This study begins to quantify the importance of a solid foundation of There have been similar studies evaluating health professional students' foundational knowledge and impact on performance in professional curricula (Robertson et al, 2019;Robertson et al, 2020;Giles et al, 2021). One such study found that an examination held within the first two weeks of a professional medical curriculum was predictive of student success in the rest of the professional curriculum (Winston et al, 2014); however, this assessment included not only anatomy, but physiology and biochemistry content as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study begins to quantify the importance of a solid foundation of There have been similar studies evaluating health professional students' foundational knowledge and impact on performance in professional curricula (Robertson et al, 2019;Robertson et al, 2020;Giles et al, 2021). One such study found that an examination held within the first two weeks of a professional medical curriculum was predictive of student success in the rest of the professional curriculum (Winston et al, 2014); however, this assessment included not only anatomy, but physiology and biochemistry content as well.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all students taking an anatomy prerequisite, and 93.1% reporting prior dissection experience, only 55.9% of respondents stated that they felt prepared for the course. This is likely explained by the fact that not all undergraduate institutions and anatomy courses are the same (Rush et al, 2005; Kogan et al, 2009; Giles et al, 2021), and therefore students may obtain different levels of foundational anatomy knowledge. Unfortunately, the data were anonymous, therefore the responses could not be directly correlated with performance on the pre‐quiz and subsequent performance in the course.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by existing research, as a preliminary survey conducted in 2014 found that approximately 80% of occupational therapy anatomy courses in the United States were taught by anatomists (Carroll & Lawson, 2014), while Latman and Lanier (2001) found that the majority of occupational therapy anatomy courses were taught by anatomists or a team of anatomist and OT. However, primary anatomy instructors varied even more widely when consid- on those systems and concepts that are less relevant to the field of occupational therapy (Schofield, 2017), while OTs alone may not feel competent enough to teach certain anatomical regions and systems, resulting in knowledge gaps in their students (Giles et al, 2021).…”
Section: Faculty Considerations When Designing Occupational Therapy A...mentioning
confidence: 99%
“…Occupational therapy is defined as, “the art and science of applying occupation as a means to effect positive, measurable change in the health status and functional outcomes of a client by a qualified occupational therapist and/or occupational therapy assistant (as appropriate)” (ACOTE, 2018). Occupations are the meaningful daily life activities in which people engage; in other words, they are everything that people do to occupy themselves, which allow them to fulfill personally and culturally relevant goals determined by their own unique interests (Salvatori, 1999; Giles et al, 2021; Silva et al, 2021). Anatomical knowledge creates the foundation for occupational therapy practitioners to evaluate their clients' current limitations and provide best‐practice interventions to enable clients to resume their participation in the roles, habits, and routines of daily occupation (Giles et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Students in the early stages of their medical degree have described anatomy as boring and relate it to learning off reams of factual information which demands self‐discipline rather than understanding the material (Bergman et al, 2013a). A recent study has indicated that 53% ( n = 87) of students, who had already completed their undergraduate degree in OT and were pursuing further OT training either by completing a Masters or a Doctorate degrees, did not feel prepared or felt only somewhat prepared for the anatomy content of a mandatory module as they lacked confidence in their anatomical knowledge gained during their undergraduate OT program (Giles et al, 2021). Schofield (2018) found that occupational therapists with more than three years' experience were of the opinion that newly graduated therapists did not possess adequate anatomy knowledge, although there is a lack of empirical data to affirm this opinion.…”
Section: Introductionmentioning
confidence: 99%